The Implementation of Defence Diplomacy in ASEAN During The COVID-19 Pandemic: Case Study of ASEAN Center of Military Medicine (ACMM) - Daos Kadati, Therenza Prasticke (Universitas Muhammadiyah Malang, 2023)
ASEAN is currently facing unprecedented security challenges during the COVID-19 pandemic since the beginning of 2020. Defence diplomacy has been playing a key role in addressing this issue. Thus, this paper aims to analyze the implementation and changes of defence diplomacy in ASEAN, particularly on ASEAN Center of Military Medicine before and during the COVID-19 pandemic. The paper found that ACMM has developed during the COVID-19 pandemic with the change in focus from disaster relief to humanitarian assistance, especially in the medical sector. The paper also found that there have been changes in the form of activities from face-to-face to virtual activities such as tabletop exercises and workshops online instead of joint training and field exercise. Keywords: COVID-19, Defence Diplomacy, ASEAN Center of Military Medicine (ACMM), ASEAN Defence Cooperation, humanitarian assistance